Uji Efektivitas Ekstrak Daun Pepaya (Carica papaya L.) dalam Bentuk Lotion sebagai Repelen Alami terhadap Nyamuk Aedes aegypti - Wiwik Yunidawati (Madani: Jurnal Ilmiah Multidisiplin, 2026)
Dengue Hemorrhagic Fever (DHF), transmitted by the Aedes aegypti mosquito, remains a significant public health problem in Indonesia. The continuous use of synthetic repellents based on Diethyltoluamide (DEET) may cause skin irritation and contribute to vector resistance. This study aimed to evaluate the effectiveness of papaya leaf (Carica papaya L.) extract lotion as a natural repellent against Aedes aegypti mosquito bites. Papaya leaf extract was obtained through the maceration method using 70% ethanol as a solvent. The lotion formulations were prepared with different concentrations of papaya leaf extract, namely F1 (5%), F2 (10%), and F3 (15%), along with a positive control (13% DEET lotion) and a negative control (lotion base without extract). The protection efficacy test was conducted on human volunteers for 6 hours with observations at 1-hour intervals. The results showed that the concentration of papaya leaf extract had a significant effect on the protective efficacy of the lotion (p < 0.05). Formulation F3 (15%) demonstrated the highest protection efficacy among the extract treatment groups, reaching 92% in the first hour and remaining above 80% until the 4th hour. The secondary metabolites in papaya leaves, such as alkaloids (carpaine), flavonoids, and tannins, play an important role as mosquito-repellent agents. It can be concluded that papaya leaf extract lotion at a concentration of 15% has the potential to be developed as an effective and safe natural repellent.